How I Live Now - Rosoff M. Meg (London, Penguin Books, 2005)
It would be much easier to tell this story if it were all about a chaste and perfect love between Two Children Against the World at an Extreme Time in History. But lets face it, that would be crap. Daisy is sent from New York to England to spend a summer with cousins she has never met. They are Isaac, Edmond, Osbert and Piper. And two dogs and a goat. Shes never met anyone quite like them before - and, as a dreamy English summer progresses, Daisy finds herself caught in a timeless bubble.It seems like the perfect summer. But their lives are about to explode. Falling in love is just the start of it. War breaks out - a war none of them understands, or really cares about, until it lands on their doorstep. The family is separated. The perfect summer is blown apart